A Micro‐pulse Process of Atomic Layer Deposition of Iron Oxide Using Ferrocene and Ozone Precursors and Ti‐Doping. Issue 4 (16th May 2013) - Li, Xianglin; Fan, Ng Chin; Fan, Hong Jin; Knez, Mato; Yong, Qin
Abstract Hematite (α‐Fe2O3) thin films are obtained by atomic layer deposition (ALD) in the temperature range 200 − 350°C using ferrocene and ozone as the precursors. A micro‐pulse process facilitates the precursor adsorption and shortens the ferrocene dose time to 5 s. When tested on Si(100) substrates, the growth rate is around 0.5 Å per cycle for the first 300 cycles, after which the growth becomes nonlinear. Interestingly, a linear growth can be maintained with a rate of ≈0.55 Å per cycle by TiO2 co‐deposition (cycle ratio of TiO2/Fe2O3 = 1:20). Characterizations by X‐ray photoemission spectroscopy (XPS), Raman spectroscopy (RS), and UV‐vis absorption confirm the presence of the α‐Fe2O3 phase after post‐deposition annealing. Uniform depositions on dense ZnO nanorod arrays and anodic aluminum oxide (AAO) templates are also demonstrated, inferring that the current process is capable of coating on high (>50) aspect ratio structures.